NILAI-NILAI BUDAYA BATAK TOBA SEBAGAI SUMBER PEMBELAJARAN IPS UNTUK MENGEMBANGKAN WAWASAN KEBANGSAAN - Eka Susanti (Metafora: Education, Social Sciences and Humanities Journal, 2020)
Dalihan na Tolu is a philosophy of life to pursue the ideals of the always rely on the value of hard work and honest. Hamoraon, hagabeon, hasangapon is a philosophy of life that people in life are required for persistent, hard-working, noble and oriented to the future. Patik dohot Uhum are rules and laws that must be followed to establish the truth and justice. Social Studies learn about the social-cultural mosaic of life can be developed through contextual learning. Community and cultural values can be used as a source of learning and laboratory to match the theoretical knowledge with practical reality. Cultural values of Batak Toba can be used as materials, learning resources, laboratory of Social Studies.